The large, the small and the human mind - Penrose, Roger; Shimony, Abner; Longair, Malcolm (Cambridge University Press, 1999)
Roger Penrose\'s views on the large-scale physics of the Universe, the small-scale world of quantum physics and the physics of the mind are controversial and widely discussed. This book is a fascinating and accessible summary of Roger Penrose\'s current thinking on those areas of physics in which he feels there are major unresolved problems. It is also a stimulating introduction to the radically new concepts that he believes will be fruitful in understanding the workings of the brain and the nature of the human mind.
Keywords: přírodní vědy; Physics; Mathematics; matematika; fyzika; fyzika, biofyzika